Construction of miRNA-mRNA network in the differentiation of chicken preadipocytes. Issue 3 (4th May 2022) - Zhang, T.; Chen, L.; Ding, H.; Wu, P.; Zhang, G.; Pan, Z.; Xie, K.; Dai, G.; Wang, J.
ABSTRACT: 1. MicroRNAs (miRNAs) play key roles in regulating lipid metabolism, adipogenesis and fat deposition in chicken. To date, there are only a few miRNAs that have been confirmed to be involved in chicken adipogenesis. The detailed mechanisms by which miRNAs regulate chicken adipogenesis remain largely unknown. 2. To identify candidate miRNAs involved in chicken preadipocyte differentiation and explore potential mechanisms behind their functions, the following study analysed and identified miRNA and mRNA expression levels in undifferentiated and differentiated preadipocytes. Hub miRNA-mRNA interactions were identified, and the degree of connectivity of DE miRNAs in the network was established. 3. A total of 145 DE miRNAs and 660 DE mRNAs were identified between undifferentiated and differentiated preadipocytes. An miRNA-mRNA network was constructed, including 29 DE miRNAs and 155 DE mRNAs, forming 470 miRNA-mRNA interactions. Functional enrichment analysis showed that DE mRNAs in the network were significantly enriched in 712 biological processes and 13 KEGG pathways. Based on the connectivity degree, five DE miRNAs with higher degrees miR-195-x, gga-miR-200a-3p, gga-miR-135a-5p, novel-m0067-5p and novel-m0270-5p were identified as hub miRNAs. Fifty-eight DE mRNAs interacted with these five hub miRNAs and formed 70 miRNA-mRNA interactions. 4. This study constructed a miRNA-mRNA network associated with chicken preadipocyte differentiation and identified five hub miRNAs in the network. The findings identified a number of chicken adipogenic miRNAs and laid the foundation for elucidating the miRNA-mediated regulatory mechanism in chicken adipogenesis.